Exploitation des couvertures photograohiques aériennes répétées du front des glaciers vêlant dans Disko Bugt et Umanak Fjord, juin-juillet 1964. - Carbonnell, M.; Bauer, A. (Meddelelser om Grønland, 1968)
The aim of the present report is Lo study the repeated photographic coverage of the front of the glaciers calving into Disko Bugt and Umanak Fjord (\Vest Greenland) taken by Danish Geodetic Institut in 1964 within the framework of the glaciological investigations of E.G.I.G. The first part shows the results of photogrammetric measurements on the clichés of photographs of 16 glaciers made by Institut Géographique National (Paris). The velocities of many transverse profiles, the position and the heights of the front are given for each glacier. The mean values of the velocity at the front range between 0,9 to 19,1 m/24 h for the Jakobshavns Isbræ. The second part is the glaciological interpretation of these results by A. BAUER . The glaciers show an acceleration of the flow towards their front. Not all glaciers present a front floating. For the glaciers with high velocity, great differences exist between the velocities measured in 1957 and in 1964. The mean velocity at the front of each glacier multiplied by the mean thickness gives the solid discharge which, for the 20 glaciers investigated, reach about 100 km3/year ± 3 %The most active, Jakobshavns Isbræ, has a solid discharge of 36,6 km3/year, which means 32,9 km3/year of water or 1045 m3/sec of water. Extrapolating the increase of the discharge of the 20 glaciers in relation to previous estimations, we obtain a figure of the total discharge of outflow glaciers of the Greenland Ice Sheet of 280 km3/year of water. The negative balance of the ice sheet reaches - 110 km3/year of water, which means a water layer of + 0,3 mm/year uniformly spread out over all seas of the globe.